1998
DOI: 10.1097/00005176-199801000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Transpyloric Enteral Feeding in Critically Ill Children

Abstract: Transpyloric enteral feeding is a good method of nutritional support in critically ill children and can be used in patients treated with neuromuscular blocking agents. The frequency and severity of complications and the risks of pulmonary infection and hepatic dysfunction related to TEF are low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The use of BNJTs is becoming more common in the paediatric intensive care setting. Several studies in paediatrics have shown that NJ feeding has facilitated successful nutritional support via the enteral route, thereby avoiding PN and reaching predicted energy requirements at a faster rate (Panadero et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The use of BNJTs is becoming more common in the paediatric intensive care setting. Several studies in paediatrics have shown that NJ feeding has facilitated successful nutritional support via the enteral route, thereby avoiding PN and reaching predicted energy requirements at a faster rate (Panadero et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The PP route may potentially reduce the risk of aspiration and, by bypassing any abnormal gastric emptying, lead to greater EN tolerance . However, the indications for PP feeding are not clear, and practice is not uniform . In addition to careful selection of patients who might benefit from PP feeding, challenges surrounding PP tube placement must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…This means that oral or nasogastric feeding is often poorly tolerated, with gastric distension and a higher risk of pulmonary aspiration, particularly in those patients on mechanical ventilation [9]. Duodenojejunal enteral nutrition has been demonstrated to be a good alternative route in critically ill adults, but there is still little experience in children [10,11].…”
mentioning
confidence: 99%